Changes in lipid composition in hippocampus early and late after status epilepticus induced by kainic acid in wistar rats - Dal-Pizzol, Felipe; Quevedo, Joao; Streck, Emilio; Walz, Roger; Moreira, Jose Claudio F. (Springer, 2007)
Oxidative damage to biological membranes has been reported as a cause of alterations in many different diseases. We had previously reported lipid peroxidation in the kainic acid model of temporal epilepsy. In this study we evaluated earlier and later modifications in the lipid composition after status epileticus induced by kainic acid. Lipid composition was determined by thin-layer chromatography, in the cortex and hippocampus 12-14 h, 7-8, 75-80, or 140-150 days after the end of status epileticus. In the hippocampus there was a significant change in the lipid protein ratio after status epileticus and this was accompanied by an alteration in lipid composition in all tested times. These results suggested that lipid peroxidation induced by kainic acid could be accompanied by chronic changes in the lipid composition that could be related to the development of seizures.
Keywords: oxidative stress; kainic acid; seizures; lipid peroxidation; lipid composition; membrane fluidity